(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aimed to reveal the possibility of predicting academic procrastination through both Cognitive distortions and time management among students of Al-Aqsa Community College, as well as to reveal the level of both cognitive distortions, time management, and academic procrastination. Additionally, it aimed to identify the size of the correlation between cognitive distortions, time management, and academic procrastination. The study sample consisted of (250) students from Al-Aqsa community college students. The results of the study concluded that the mean for each level of cognitive distortions and academic procrastination is average. The mean level of time management is high. There is a statistically significant positive relationship between cognitive distortions and their dimensions and academic procrastination. There is a statistically significant negative relationship between both time management and its dimensions and academic procrastination. Cognitive distortions, time management, and their dimensions contribute to an acceptable average in predicting academic procrastination.